Beyond mixed methods: a pluralist approach to objects in interdisciplinary teaching and learning - Rune Bolding Bennike; Katrine Ellemose Lindvig (Humanities & Social Sciences Communications)
Abstract The study of objects holds a central place in research on interdisciplinary research practices, yet we know little about the role of objects in facilitating or hindering interdisciplinary learning in higher education. This article develops a pluralist, relational, and dynamic approach to studying the role of objects in interdisciplinary teaching and learning. We document the potential for objects to perform different functions depending on how they are employed and engaged in educational settings. Based on a small, exploratory case study of teaching-learning dynamics at an interdisciplinary MSc course, we examine the roles performed by three very different objects: the dominant object of mixed methods, an interdisciplinary mapping exercise introduced by the teacher, and the spontaneously emerging epistemic object of “perceptions”. We find clear limitations of the dominant mixed-methods approach to interdisciplinarity: while the approach provides a simple and efficient way to organize interdisciplinary collaboration, it risks reinforcing disciplinary boundaries rather than enabling their crossing. Although this gives students the impression of doing interdisciplinary work—and enables them to do so at a relatively superficial level—it simultaneously undercuts the potential for deeper learning. In contrast, we found the “epistemic” object of “perceptions”, that surfaced spontaneously in a student discussion, provided opportunities for transformative understanding across disciplines. We conclude the paper with some reflections on the learning potential of troublesome differences and our role as teachers in balancing improvisation and scaffolding to stimulate deeper interdisciplinary learning beyond mixed methods. In our discussion, we draw upon the concept of threshold concepts to better understand how objects can variously serve as bridges for communication or as portals to more profound interdisciplinary understanding, suggesting new directions for research on objects in teaching and learning contexts.